Prospective cohort study of influenza vaccine effectiveness among healthcare personnel in Lima, Peru: Estudio Vacuna de Influenza Peru, 2016‐2018. Issue 4 (5th April 2020) - Wesley, Meredith G.; Soto, Giselle; Arriola, Carmen Sofia; Gonzales, Miriam; Newes‐Adeyi, Gabriella; Romero, Candice; Veguilla, Vic; Levine, Min Z.; Silva, Maria; Ferdinands, Jill M.; Dawood, Fatimah S.; Reynolds, Sue B.; et al.
Abstract: Background: The Estudio Vacuna de Influenza Peru (VIP) cohort aims to describe the frequency of influenza virus infection, identify predictors of vaccine acceptance, examine the effects of repeated influenza vaccination on immunogenicity, and evaluate influenza vaccine effectiveness among HCP. Methods: The VIP cohort prospectively followed HCP in Lima, Peru, during the 2016‐2018 influenza seasons; a fourth year is ongoing. Participants contribute blood samples before and after the influenza season and after influenza vaccination (for vaccinees). Weekly surveillance is conducted to identify acute respiratory or febrile illnesses (ARFI). When an ARFI is identified, participants self‐collect nasal swabs that are tested for influenza viruses by real‐time reverse transcriptase‐polymerase chain reaction. Influenza vaccination status and 5‐year vaccination history are ascertained. We analyzed recruitment and enrollment results for 2016‐2018 and surveillance participation for 2016‐2017. Results: In the first 3 years of the cohort, VIP successfully contacted 92% of potential participants, enrolled 76% of eligible HCP, and retained >90% of participants across years. About half of participants are medical assistants (54%), and most provide "hands‐on" medical care (76%). Sixty‐nine percent and 52% of participants completed surveillance for >70% of weeks in years 1 and 2, respectively. Fewer weeks of completed surveillance was associated with older age (≥50 years), being a medical assistant, self‐rated health of fair or poor, and not receiving the influenza vaccine during the current season ( P ‐values < .05). Conclusions: The VIP cohort provides an opportunity to address knowledge gaps about influenza virus infection, vaccination uptake, effectiveness and immunogenicity among HCP.